IMPLEMENTATION OF GENDER MAINSTREAMING IN WOMEN'S PROTECTION POLICY IN SIAK DISTRICT - Firdaus, Emilda; Andrikasmi, Sukamarriko; Haryono, Dodi; Indra, Mexsasai; Artina, Dessy; HB, Gusliana (Indonesian Journal of Economics, Social, and Humanities, 2024)
Women are a group or group that is vulnerable to violence that occurs in society. To overcome various issues of violence that occur against women, special attention is needed from all groups, both community groups and government circles, consisting of the central government and regional governments. This certainly has an impact on the existence of women's groups in the social order amidst demands for achieving Sustainable Development Goals (SDG's). If we refer to the concept of "mainstreaming" itself, it can be interpreted as a process that is carried out to bring aspects that were previously considered unimportant or marginal into the decision-making and management of main institutional activities and work programs. This series of strategies was prepared based on insight, critical awareness and data obtained from gender analysis. Therefore, this study is considered important to look at gender representation in Siak Hijau policies.